2006
DOI: 10.1093/ndt/gfl243
|View full text |Cite
|
Sign up to set email alerts
|

Role of integrin-linked kinase in epithelial–mesenchymal transition in crescent formation of experimental glomerulonephritis

Abstract: The present results provide the first evidence that expression and activity of ILK are increased in cellular crescents of experimental GN. Enhanced expression and activity of ILK, possibly by TGF-beta1, is associated with the induction of EMT by PEC and thereby, may participate in the formation of cellular crescents in GN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 39 publications
1
32
1
1
Order By: Relevance
“…However, the detailed mechanism that ILK is involved in TIF is still not well understood. Shimizu et al [28] suggested that the role of ILK in TIF might associate with EMT. They found that enhanced expression and activity of ILK was associated with the induction of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…However, the detailed mechanism that ILK is involved in TIF is still not well understood. Shimizu et al [28] suggested that the role of ILK in TIF might associate with EMT. They found that enhanced expression and activity of ILK was associated with the induction of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤ 1 is also strongly expressed in the cellular crescents [19] ( table 1 ). In human IgAN, where mesangial cell is the target of injury, mesangial immunostaining for active TGF-␤ 1 is almost negligible, despite increased mesangial TGF-␤ 1 mRNA levels.…”
Section: Tgf-␤ Expression In Hyperplastic Podocytes In the Diseased Gmentioning
confidence: 98%
“…In the TGF-␤ 1 transgenic mice, an acute and massive increase in plasma levels of TGF-␤ 1 results in severe GN with occasional crescent formation [17,18] . Indeed, TGF-␤ 1 is strongly expressed in the cellular crescents in the early stage of experimental crescentic GN [19] . Furthermore, podocytes covering the cellular lesion of FSGS exhibit increased expression of TGF-␤ 1 protein in human glomerular diseases [20,21] , and in Denys-Drash syndrome (DDS) mice [15] .…”
Section: Introductionmentioning
confidence: 98%
“…Growing evidence suggests that ILK is a critical mediator for tubular EMT induced by TGF-β 1 and CTGF [26,27,28], and likely plays a crucial role in podocyte damage, proteinuria and the pathogenesis of chronic renal fibrosis [29,30,31]. Forced expression of ILK in proximal tubular epithelial cells suppressed E-cadherin expression and induced fibronectin expression and its extracellular assembly [26].…”
Section: Introductionmentioning
confidence: 99%